Edukasi Pemanfaatan Buah Golden Berry Guna Meningkatkan Nilai Ekonomi di Kampung KB Layang-Layang - Annisa Ramadhani; Nur Afifah; Sifa Afiq Nurrahman; Yustika Amanda; Mona Lestari (Universitas Lancang Kuning, 2022)
The location of this service is in Kampung KB Layang-Layang. In this village found natural wealth which is natural resources of the Golden Berry plant. Golden Berry is a wild plant that contains many benefits, which is health benefits that can increase the economic value of the community. However, understanding regarding the Golden Berry in Kampung KB Layang-Layang is still lacking. Therefore community empowerment is needed regarding the Golden Berry plant to support the utilization and processing the content of the Golden Berry, especially the fruit. Moreover, lack of Golden Berry cultivators due to dense environmental conditions, has become one of the focus problems that are solved through cultivation using polybags and utilizing local community yard. Based on the conditions that occur, then formed activities that are able to maximize the potential of the Golden Berry plant in the Kampung KB Layang-Layang, that is counseling, training, mentoring, and controlling